Analisis SWOT Dalam Menentukan Strategi Pemasaran Warung Angkola Kopi Sipirok Kabupaten Tapanuli Selatan - Halman Paris Ritonga; Yossar; Erianto (Riset Sinergi Indonesia, 2024)
The purpose of this study is to determine the right marketing strategy for businesses at Warung Angkola Kopi Sipirok Tapanuli Selatan through a SWOT analysis. Therefore, the authors are interested in conducting research with the formulation of the problem. First, how is the marketing strategy for the business at the Warung Angkola Kopi Sipirok Tapanuli Selatan. Second, how is the SWOT analysis in determining the right marketing strategy for the Warung Angkola Kopi Sipirok Tapanuli Selatan business. This research is a field research with qualitative research type. To analyze the data using the IFAS, EFAS, SWOT matrix. The results of this study conclude that Warung Angkola Kopi Sipirok Tapanuli Selatan in terms of product, price, procces, place, promotion and people, phisycal eviden Warung Angkola Kopi Sipirok Tapanuli Selatan has implemented a strategy that is right on target with the company's goals. However, the physical evidence of Warung Angkola Kopi Sipirok Tapanuli Selatan did the wrong strategy so it needed to be evaluated. The strategy that can be used is the Warung Angkola Kopi Sipirok Tapanuli Selatan based on the SWOT matrix, namely by maximizing promotions in online or offline media, prioritizing consumer satisfaction with product quality and affordable prices.